Methodology of self-managed environmental education, community La Camorra Viñales, Cuba (Revista LIDER, 2020)
This study summarizes research conducted in the community, "The Camorra" municipality Viñales, Pinar del Rio, Cuba. It proposes a methodology for self-organized environmental education, based on the participatory role of the people in the management of environmental education processes. Different measuring instruments among which are surveys, brainstorming and focus group were used; concluding that through the application of the methodology a high degree of involvement can be achieved in the population, and it is consciously involved in the processes of selfmanaged environmental education in the community.